The influence of cartoons on attitudes to science and to being a scientist - doi: 10.4025/actascilangcult.v35i2.17551 - Paula Cavalcante Monteiro; Ourides Santin-Filho (Universidade Estadual de Maringá, 2013)
Television is a powerful vehicle of mass communication and several cartoons, specifically made for children and adolescents, have 'scientific' themes. Preteens and teens devote many hours in front of TV, attracted by cartoons, some of which portray, in a caricature manner, scientists at work. Current paper investigates the effect the concepts of science transmitted by the cartoon 'Jimmy Neutron' have on adolescents. A group of 31 adolescents of the 9th grade of the junior school were invited to watch three episodes of the 'Jimmy Neutron' cartoon. After the sessions, they answered a questionnaire and were interviewed on their perceptions of Science and scientists. Their answers were analyzed by Discourse Textual Analysis. Results show that they most have misconceptions on Science and on scientists and they presume that scientists have a very solitary and uninterested life solely dedicated in investing new devises.